Probiotics: The scientific evidence in the context of inflammatory bowel disease. Issue 9 (13th June 2017) - Celiberto, Larissa Sbaglia; Bedani, Raquel; Rossi, Elizeu Antonio; Cavallini, Daniela Cardoso Umbelino
Abstract: Inflammatory bowel disease (IBD) generally comprises Crohn's disease (CD) and ulcerative colitis (UC), and their main characteristic is the intestinal mucosa inflammation. Although its origin is not yet fully known, there is growing evidence related to genetics, intestinal microbiota composition, and the immune system factors such as precursors for the initiation and progression of intestinal conditions. The use of certain probiotic microorganisms has been touted as a possible and promising therapeutic approach in reducing the risk of inflammatory bowel disease, specifically ulcerative colitis. Several mechanisms have been proposed to explain the benefits of probiotics, indicating that some bacterial strains are able to positively modulate the intestinal microbiota and the immune system, and to produce metabolites with anti-inflammatory properties. The aim of this paper is to bring together the various results and information, based on scientific evidence, that are related to probiotics and inflammatory bowel disease, emphasizing the possible mechanisms involved in this action.